New Roman Participation, Acceptance, And Motivation of Students to In-Class Game-Based Learning (GBL) - Elisabete S. VIEIRA; Mara MADALENO; Daniel MAGUETA (Communications of International Proceedings, 2022)
This study intends to contribute to the analysis of the use of Game-Based Learning (GBL) platforms, and their effects on the acquisition of skills by students. For the effect reviews, some of the literature reported results to build a theory of competencies acquisitions through GBL. Results indicate that GBL helps the learning process to be more effective, namely reducing asymmetries in achievement, improving students’ attitudes, and behavior, helping them retain more information and knowledge longer; enhancing the level of student interest toward the subject being studied, as well as increasing students’ motivation and reducing their learning anxiety.
Keywords: Game-Based Learning; Problem Solving; Skills; Competencies; Attitudes; Participation; Motivation; Students